Is there a link between carbamylation and citrullination in periodontal disease and rheumatoid arthritis?. Issue 6 (June 2015) - Bright, R.; Proudman, S.M.; Rosenstein, E.D.; Bartold, P.M.
Abstract: The remarkable similarity in inflammatory response and pathology of periodontal disease and rheumatoid arthritis has been recognized for several decades. However, how these two disease may be interrelated has been less clear. During the pathogenesis of rheumatoid arthritis there is a preclinical immunological phase which precedes the clinical manifestation of rheumatoid arthritis. During this phase serum autoantibodies appear many years before the clinical signs and symptoms of rheumatoid arthritis become apparent. To date, the two best studied autoantibodies have been rheumatoid factor and anti-citrullinated protein antibodies (ACPA). Of these the production of ACPA has been considered very important due to their high predictive value in future manifestation of rheumatoid arthritis. Citrullination is a common post-translational modification of proteins based on the enzymatic conversion of arginine into citrulline. Extra-articular citrullination and production of ACPA, as a priming immunological experience, is well documented in many tissues including the inflamed gingival tissues associated with periodontal disease. More recently, carbamylation of proteins has also been implicated in the pathogenesis of rheumatoid arthritis in a manner similar to citrullination. Carbamylation is a post translational modification of proteins by an enzyme-independent modification of lysine residues against which autoantibodies are subsequently induced. In this article we hypothesise that, like citrullination, carbamylation of proteins and associated antibody production during the gingival inflammation associated with gingivitis and periodontitis may play a role in the pathogenesis of rheumatoid arthritis.